The conservative cysteines in transmembrane domain of AtVKOR/LTO1 are critical for photosynthetic growth and photosystem II activity in Arabidopsis - Du, Jia-Jia; Zhan, Chun-Yan; Lu, Ying; Cui, Hao-Ran; Wang, Xiao-Yun (Frontiers in Plant Science, 2015)
Thylakoid protein vitamin K epoxide reductase (AtVKOR/LTO1) is involved in oxidoreduction. The deficiency of this compound causes pleiotropic defects in Arabidopsis thaliana, such as severely stunted growth, smaller sized leaves, and delay of flowering. Transgenic complementation of wild-type AtVKOR (VKORWT) to vkor mutant lines ultimately demonstrates that the phenotype changes are due to this gene. However, whether AtVKOR functions in Arabidopsis through its protein oxidoreduction is unknown. To further study the redox-active sites of AtVKOR in vivo, a series of plasmids containing cysteine-mutant VKORs were constructed and transformed into vkor deficient lines. Compared with transgenic AtVKORWT plants, the size of the transgenic plants with a single conservative cysteine mutation (VKORC109A, VKORC116A, VKORC195A, and VKORC198A) were smaller, and two double-cysteine mutations (VKORC109AC116A and VKORC195AC198A) showed significantly stunted growth, similar with the vkor mutant line. However, mutations of two nonconservative cysteines (VKORC46A and VKORC230A) displayed little obvious changes in the phenotypes of Arabidopsis. Consistently, the maximum and actual efficiency of photosystem II in double-cysteine mutation plants decreased significantly to the level similar to that of the vkor mutant line both under normal growth light and high light. A significantly decreased amount of D1 protein and increased accumulation of reactive oxygen species were observed in two double-cysteine mutations under high light. All of the results above indicated that the conservative cysteines in transmembrane domains were the functional sites of AtVKOR in Arabidopsis and that the oxidoreductase activities of AtVKOR were directly related to the autotrophic photosynthetic growth and photosystem II activity of Arabidopsis thaliana.